Project to Production: Digital Preservation at the Houses of Parliament, 2010–2020 - Christopher Fryer (International Journal of Digital Curation, 2015)
The Parliamentary Archives is responsible for preserving and providing access to the historical records of the UK Parliament, a collection of national, and indeed international, importance which encompasses a wide range of digital content, created and used in an ever changing environment. Since 2010 a staged project has led to the successful implementation of an operational digital repository. The transition from project to production allows the Parliamentary Archives to reflect on the organisation’s progress in digital preservation. However, the deployment of a production digital repository also allows the Parliamentary Archives to outline future goals. The project has demonstrated the viability of implementing digital preservation infrastructure. The challenge remains to embed digital preservation as a business as usual activity.